Differences of Colostrum Production in Fore and Rear Teat of FHC Dairy Cows - Zahwa Fajriyyah Eka Putri; Puguh Surjowadojo (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
This research aims to comprehend the different colostrum production between the fore and rear teats of FHC dairy cows. The method used was a case study by observing and collecting data at a farm by purposive sampling. The materials used in this study were 41 postpartum FHC dairy cows that produce colostrum on days 1-4 with a lactation period of 1-5. The data were tabulated and analyzed using paired t-test. The results showed that the average production of colostrum on the fore teats were 6.40 Â± 5.39 kg/cow/day and the production of colostrum rear the teats were 7.03 Â± 5.92 kg/cow/day and the highest average production of colostrum was on 3rd lactation period. The conclusion of the analysis showed that the production of colostrum in the fore and rear teats were highly different because the rear teats are larger than the fore teats.